TÜRK İNANÇ SİSTEMİNDE YARATIMIN ÜÇ AYAĞI: SU, AY VE KADIN. - YURDAKUL, NAGİHAN BAYSAL (Turkish Culture & Haci Bektas Veli Research Quarterly, 2026)
This article argues that within the Turkish belief system, the phenomenon of creation is not conceived as a linear and singular moment of beginning, but rather as a process operating within a network of continuity and cyclicality. The theoretical framework of the study is based on the assumption that the elements explaining creation should be examined not as independent symbolic elements, but as a relational whole that produces and transforms each other. Accordingly, water, the moon, and woman are considered the three fundamental components of creation in the Turkish cosmological conception, and the functions of each element on ontological, temporal, and bodily planes are analyzed. Water represents the cosmic ground of creation as the primordial substance and potential carrier of existence; the moon ensures the continuity of creation as a rhythmic regulator establishing the cyclical understanding of time; and woman reveals the concrete and experiential manifestation of creation through fertility, transformation, and bodily experience. The study demonstrates that these three elements do not remain solely at the level of mythical narratives; they are reproduced through rituals, beliefs, and daily practices, thus ensuring that creation is embedded in cultural memory as an ongoing process. This approach, developed through relational reading, demonstrates that in the Turkish belief system, creation exhibits a holistic structure that simultaneously intersects cosmic, social, and bodily planes. Therefore, it is emphasized that creation should not be considered merely as a narrative of a beginning, but rather as a continuous process of becoming.